Burden of Vitamin D, Vitamin B12 and Folic Acid Deficiencies in an Aging, Rural Indian Community - Sundarakumar, Jonas S.; Shahul Hameed, Shafeeq K.; , SANSCOG Study Team; Ravindranath, Vijayalakshmi (Frontiers in Public Health, 2021)
Introduction: The important role of micronutrient deficiencies in aging-related disorders including dementia is becoming increasingly evident. However, information on their burden in India is scarce, especially, among aging and rural communities. Methods: Prevalence of vitamin D, B12 and folic acid deficiency was measured in an ongoing, aging cohort, from rural India – Srinivaspura Aging Neurosenescence and COGnition (SANSCOG) study cohort. Serum level estimation of vitamin D, B12 and folic acid, using chemiluminescence immunoassay, was performed on 1648 subjects (872 males, 776 females). Results: Mean vitamin D, B12 and folic acid levels were 23.4 ± 10.6 ng/ml, 277.4 ± 194.4 pg/ml and 6 ± 3.5 ng/ml), respectively. Prevalence of low vitamin D (< 30 ng/ml), vitamin D deficiency (< 20 ng/ml), B12 deficiency (< 200 pg/ml) and folic acid deficiency (< 3 ng/ml) were 75.7%, 39.1%, 42.3% and 11.1%, respectively. Significantly more women had vitamin D deficiency, whereas more men had folic acid deficiency. Women belonging to the oldest age group (≥ 75 years) had the maximum burden of low vitamin D (94.3%) and folic acid deficiency (21.8%). Discussion: Older, rural-dwelling Indians have high burden of vitamin D and B12 deficiencies, which is concerning given the potentially negative consequences on cognition, immunity and frailty in the aging population. Urgent public health strategies are needed to address this issue and prevent or mitigate adverse consequences.